Bismuth oxide aqueous colloidal nanoparticles inhibit Candida albicans growth and biofilm formation - Cabral Romero, Claudio; Hernández Delgadillo, René; Velasco Arias, Donaji; Martínez Sanmiguel, Juan José; Diaz, David; Zumeta Dube, Inti; Niño Arevalo, Katiushka (2013)
Abstract: Multiresistance among microorganisms to common antimicrobials has become one of the most significant concerns in modern medicine. Nanomaterials are a new alternative to successfully treat the multiresistant microorganisms. Nanostructured materials are used in many fields, including biological sciences and medicine. Recently, it was demonstrated that the bactericidal activity of zero-valent bismuth colloidal nanoparticles inhibited the growth of Streptococcus mutans; however the antimycotic potential of bismuth nanostructured derivatives has not yet been studied. The main objective of this investigation was to analyze the fungicidal activity of bismuth oxide nanoparticles against Candida albicans, and their antibiofilm capabilities. Our results showed that aqueous colloidal bismuth oxide nanoparticles displayed antimicrobial activity against C. albicans growth (reducing colony size by 85%) and a complete inhibition of biofilm formation. These results are better than those obtained with chlorhexidine, nystatin, and terbinafine, the most effective oral antiseptic and commercial antifungal agents. In this work, we also compared the antimycotic activities of bulk bismuth oxide and bismuth nitrate, the precursor metallic salt. These results suggest that bismuth oxide colloidal nanoparticles could be a very interesting candidate as a fungicidal agent to be incorporated into an oral antiseptic. Additionally, we determined the minimum inhibitory concentration for the synthesized aqueous colloidal Bi2 O3 nanoparticles.